Automated Usability Evaluation during Model-Based Interactive System Development - Feuerstack, Sebastian; Blumendorf, Marco; Kern, Maximilian; Kruppa, Michael; Quade, Michael; Runge, Mathias; Albayrak, Sahin (Engineering Interactive Systems, 2008)
In this paper we describe an approach to efficiently evaluate the usability of an interactive application that has been realized to support various platforms and modalities. Therefore we combine our Multi-Access Service Platform (MASP), a model-based runtime environment to offer multimodal user interfaces with the MeMo workbench which is a tool supporting an automated usability analysis. Instead of deriving a system model by reverse-engineering or annotating screenshots for the automated usability analysis, we use the semantics of the runtime models of the MASP. This allows us to reduce the evaluation effort by automating parts of the testing process for various combinations of platforms and user groups that should be addressed by the application. Furthermore, by testing the application at runtime, the usability evaluation can also consider system dynamics and information that are unavailable at design time.